2007
DOI: 10.1080/10929080701536046
|View full text |Cite
|
Sign up to set email alerts
|

Computer assisted pelvic tumor resection and reconstruction with a custom-made prosthesis using an innovative adaptation and its validation

Abstract: Computer aided musculoskeletal tumor surgery is a novel concept. Ideally, computer navigation enables the integration of preoperative information concerning tumor extent and regional anatomy to facilitate execution of a surgical resection. Accurate resection helps oncological clearance and facilitates precise fitting of a custom prosthesis. We adapted a commercially available computer navigation platform for spine, and used it to plan and execute pelvic bone resection and custom pelvic prosthetic reconstructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 0 publications
1
21
1
1
Order By: Relevance
“…Fusion images were considered valuable if additional information not seen on conventional images was obtained for resection planning. Intraoperative navigation has been described [17,18]. The image-to-patient registration to match the corresponding points between the patient's real intraoperative anatomy and preoperative CT images was performed by paired points and surface matching.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion images were considered valuable if additional information not seen on conventional images was obtained for resection planning. Intraoperative navigation has been described [17,18]. The image-to-patient registration to match the corresponding points between the patient's real intraoperative anatomy and preoperative CT images was performed by paired points and surface matching.…”
Section: Methodsmentioning
confidence: 99%
“…Computed tomography (CT)-based navigation for pelvic tumor resection and reconstruction with a custom pelvic prosthesis was reported to be successful [18].…”
Section: Introductionmentioning
confidence: 99%
“…The two-dimensional (2D)/three-dimensional (3D) fused images enable a detailed delineation of tumor margins, allowing precise definition of the plane of intended bone resection. In a case report, Wong et al [8] showed the results in a patient with a periacetabular resection and reconstruction with a custom-made pelvic prosthesis using the CATS technique, which incorporated both the planes of intended resection and the location of the pelvic prosthesis at the navigation planning stage. Preoperative navigation planning that includes complete information about resection and reconstruction may be implemented via intraoperative navigation guidance.…”
Section: Overview Of Cats In Orthopedic Oncologymentioning
confidence: 99%
“…Interestingly, software solutions for navigated pelvic surgery are rare. In previous pelvic studies, the navigation techniques were adapted from other areas such as the spine to the pelvic area .…”
Section: Discussionmentioning
confidence: 99%